Revisiting minority stress theory to understand psychological distress among Czech sexual minorities - Pitoňák, Michal; Csajbók, Zsófia (Studia Psychologica: Theoria et praxis, 2022)
Minority stress theory explains psychological vulnerability in sexual minorities; however, data is scarce in the Central and Eastern European region. Combining the minority stress model with the Psychological Mediation Framework, we tested a theoretically developed path model. Participants were 1452 (Mage = 24.9 years) Czech sexual-minority individuals (38.7% gay, 27.1% lesbian, 18.7% bisexual women). The model explained 55.5% of the variance of psychological distress in the overall sample, representing a total effect of 9.75% (p < .001) increase in measurement units by the modeled associations. Within the subsamples, the associations were similar between harassment and rejection, stigma awareness, and rejection sensitivity, as well as emotional dysregulation, rumination, and psychological distress. However, internalized homonegativity was a stronger factor of psychological well-being in gay men and lesbian women than in bisexual women. Bisexual women may have experienced less social support and more emotional dysregulation due to more concealment and rejection sensitivity, respectively. While we confirmed that the minority stress model applies to the Czech context and explained well psychological distress in sexual minorities, our data highlights notable differences between bisexual women who reported highest rates of distress compared to gay men and lesbian women.